"An Instrument for Reaching Into Experience": Progressive Film at the Rockefeller Boards, 1934–1945. Issue 2 (16th January 2015) - Aitken, Rob
Abstract: The emergence of progressive filmmaking in the interwar period is often associated with John Grierson, the British documentary movement and the influence it traced abroad. This paper argues, however, that more particular attention needs to attend the specific context for progressive filmmaking in the United States. To make this argument, this paper foregrounds two strands of progressive filmmaking that were pursued alongside, and often in tension with each other at the Rockefeller Boards between 1934 and 1945. The Rockefeller Boards pursued both a version of social‐realist documentary in the Griersonian tradition as well as a project focused on "human relations" films. As this paper suggests, the human relations project contrasted with Grierson's social documentary by linking film to a particular kind of psychological interior; a self not oriented to the social world but to the internal spaces of psychological and personality development. This implies a complex process of cultural diffusion in which Grierson's model was filtered through, and ultimately displaced by, a set of concerns and preoccupations unique to the American context.